Pre-stenting for Retrograde Intrarenal Surgery: Need and Duration: a Prospective Randomized Clinical Study - Chhettri, Prakash; Shrestha, Anil; Basnet, Robin Bahadur; Shrestha, Parash Mani (Nepalese Medical Journal, 2020)
Introduction: To evaluate if retrograde intrarenal surgery with ureteral access sheath requires prestenting. In case pre-stenting becomes an option, how long does it need to be stented. Materials and Methods: After obtaining approval from Institutional Review Board and informed consent, a prospective randomized controlled study was conducted in the Department of Urology, Bir Hospital for 18 months. All the patients enrolled for retrograde intrarenal surgery were grouped into 3 groups: Group 1 – without pre-stenting, Group 2 – one week of pre-stenting, and Group 3 – two weeks of pre-stenting. Success was defi ned as an ability to accommodate a 10/12 F ureteral access sheath during retrograde intrarenal surgery. Ureteral access sheath induced ureteric wall injury was also taken into consideration. Results: Among 179 cases, 152 cases were included in the study. In 36 patients out of 53 (67.92%) in group 1, 10/12 F ureteral access sheath was negotiable without pre-stenting, marking the frequency of distensible ureters. In 44 patients out of 47 (93.66%) from group 2 and all 52 patients (100%) from group 3, ureteral access sheath placement was successful after one and two weeks of pre-stenting respectively. Ureteric wall injury of grade1 and 2, was found in 9 patients (5.9%). Conclusions: The majority of ureters (67.92%) are distensible, not requiring pre-stenting before retrograde intrarenal surgery. One and two weeks of pre-stenting carries a success rate of 93.66% and 100% respectively.